Numerical and analytical method of calculation of dynamic strength of modernized air springs for high-speed electric trains - Khromova, Galina; Makhamadalieva, Malika (E3S web of conferences, 2024)
The article presents a new design of a pneumatic suspension device for the high-speed electric train “AFROSIAB”, Uzbekistan. The authors developed a numerical-analytical method for the calculation of dynamic strength of modernized pneumatic springs for high-speed electric trains; an algorithm and a program for the Mathcad 15 programming environment were built. The design given in the article is protected by the Patent of the Republic of Uzbekistan for invention No. IAP 04632 [1].